2020
DOI: 10.3389/fmed.2020.00003
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Fertility Preservation Strategies in Turner Syndrome

Abstract: Growth retardation and gonadal dysgenesis are two of the most important clinical manifestations of Turner syndrome (TS). As premature ovarian failure generally occurs early in life in women with TS, these patients should be counseled and evaluated as early as possible for discussion of optimal and individualized fertility preservation strategies. Infertility seriously affects the quality of life of women with TS. For those who have ovarian reserve, the theoretical options for future fertility in TS patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Finally, oocyte retrieval is performed transvaginally under general anaesthesia. Transabdominal retrieval is feasible, but not recommended (50). In vitro maturation (IVM) is used to increase the yield of mature oocytes.…”
Section: Oocyte Cryopreservation (Oc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, oocyte retrieval is performed transvaginally under general anaesthesia. Transabdominal retrieval is feasible, but not recommended (50). In vitro maturation (IVM) is used to increase the yield of mature oocytes.…”
Section: Oocyte Cryopreservation (Oc)mentioning
confidence: 99%
“…Vitrified oocytes show similar fertilization and pregnancy rates comparing to fresh oocytes (51). Due to small yields in TS women, additional stimulations cycles are often required for a minimal number of 10 mature oocytes (50).…”
Section: Oocyte Cryopreservation (Oc)mentioning
confidence: 99%
See 1 more Smart Citation
“…While the exact mechanism of follicular depletion is unknown, it is believed to be due to accelerated apoptosis of germ cells in the intrauterine growth period. 43 When evaluating the number of ovarian follicles in human fetuses with 45,X karyotype, studies revealed that while there are normal numbers of germ cells in the early gestational period, by midgestation their numbers were decreased significantly. 44,45 This is in part due to the high incidence of follicle apoptosis.…”
Section: Turner's Syndromementioning
confidence: 99%
“…49,62 Additionally, adolescents may not be able to tolerate ovarian stimulation or transvaginal oocyte retrieval and transabdominal oocyte retrieval is generally not recommended. 43 Due to the challenges of oocyte cryopreservation, some have advocated for in vitro matured oocyte cryopreservation. But there has only been one case report of a TS patient undergoing in vitro oocyte cryopreservation and the pregnancy potential of in vitro matured oocytes has not been shown in women with TS; so, the potential benefit to this approach is unknown.…”
Section: Turner's Syndromementioning
confidence: 99%